Separation and recovery of proteins and sugars from Halloumi cheese whey - Galanakis, Charis M.; Chasiotis, Stathis; Botsaris, George; Gekas, Vassilis (My University, 2014)
Halloumi is the traditional cheese of Cyprus that is produced using typically two processes: milk coagulation and pressed curd cooking. Both processes generate two whey substrates rich in proteins and sugars. The scope of the current study is to investigate the separation and recovery of these compounds by processing samples with a cross-flow ultrafiltration module and five membranes in two sequential steps. Three membranes (100, 50 and 20. kDa) were tested in the first scenario and 20. kDa-permeates were assayed in the second using the two materials with narrower pores of 2 and 1. kDa. Experiments were conducted under constant temperature, circulation flux and several transmembrane pressures, while recovery monitoring was performed by determining operation parameters and retention of proteins, reducing and non-reducing sugars. Results indicated that ultrafiltration is able to separate the target compounds optimally upon two different approaches: using a 100. kDa-polysulphone barrier or by combining 20. kDa-polysulphone and 2. kDa-polyethersulphone membranes. The recovery of proteins in the first approach was high for both samples (69-76%), while the retention of non-reducing sugars (herein expressed mainly lactose) was negligible (2-7%). Using the combined treatment, the recovery of proteins and non-reducing sugars was almost quantitative (87-90%) and rather low (39-32%), respectively.
Keywords: Lactose; Membrane; Nanofiltration; Protein; Ultrafiltration; Whey